ORIENTATION OF CHILDREN WITH HEARING IMPAIRMENTS TO INCLUSIVE EDUCATION (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The education system is becoming increasingly modern, providing equal opportunities for every child. In this context, inclusive education, based on the creation of a convenient and modern system in which every student can realize their potential, is an important issue. This article will examine the basic principles of inclusive education, its challenges, and solutions for integrating children with hearing impairments into inclusive education.